2019
DOI: 10.1021/acs.jafc.9b05808
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Organic Anion Transporter 3-Mediated Uptake of Steviol Acyl Glucuronide, a Major Metabolite of Rebaudioside A, with Selected Drugs

Abstract: Organic anion transporter 3 (OAT3) plays a critical role in the renal excretion of many xenobiotics. Because steviol acyl glucuronide (SVAG), an OAT3 substrate, is the major circulating metabolite after oral ingestion of steviol glycosides and is excreted into the urine, inhibition of OAT3 activity may alter pharmacokinetic profiles of SVAG. The present study showed that drugs such as probenecid and glimepiride displayed potent inhibition toward the OAT3-mediated SVAG transport, with IC 50 values of 4.9 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Regarding the elimination pathway for HDA, hepatic metabolism could provide a major contribution to the body. First, approximately 55% of the administered dose of d-HDA was recovered in the liver at 5 min, which agrees with previous observations that 35 S-labeled 2-mercapto-1,16-HDA is predominantly distributed in the liver rather than in the kidney. 38 Endogenous HDA has been suggested to be synthesized by the u-oxidation of palmitic acid, 39,40 and the enzymes involved have been characterized in various organs, including the liver, brain, lung, and kidney.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the elimination pathway for HDA, hepatic metabolism could provide a major contribution to the body. First, approximately 55% of the administered dose of d-HDA was recovered in the liver at 5 min, which agrees with previous observations that 35 S-labeled 2-mercapto-1,16-HDA is predominantly distributed in the liver rather than in the kidney. 38 Endogenous HDA has been suggested to be synthesized by the u-oxidation of palmitic acid, 39,40 and the enzymes involved have been characterized in various organs, including the liver, brain, lung, and kidney.…”
Section: Discussionsupporting
confidence: 91%
“…Many OAT3 substrates with high K m values have demonstrated in vivo interactions due to inhibition. Those substrates include but not limited to steviol acyl glucuronide with K m of 368.1 µM (Zhou et al, 2020), mesna with K m of 390 µM (Cutler et al, 2012), and isoniazid with K m of 233.7 µM (Parvez et al, 2018). Judging from quantitative proteomic data, both OAT3 and OAT1 are highly and equally expressed in human kidney, whereas OATPs are below detection limits (Prasad et al, 2016;Uchida et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A human pharmacokinetic study indicated that probenecid could markedly increase systemic exposure of enalapril and enalaprilat by decreasing their renal excretion (Noormohamed et al, 1990). As probenecid is a well characterized inhibitor of OAT3 (Tahara et al, 2006;Zhou et al, 2020), it could be assumed that the interaction between probenecid and enalapril/enalaprilat might be associated with OAT3-mediated renal clearance, although no direct evidence on OAT3's involvement was described.…”
Section: Introductionmentioning
confidence: 99%
“…The AUC 6–8h of steviol acyl glucuronide was increased to 2.9- or 2.5-fold, respectively. Therefore, people with impaired renal function should be cautious when taking steviol glycoside products [ 59 ].…”
Section: Oat3 and Herb–drug Interactions (Hdis)mentioning
confidence: 99%